(untitled) (Bangladesh Journal of Nuclear Medicine, 2015)
Different radionuclides are emitted from the reactor core after the nuclear accident. These radionuclides are entered into human body through different pathways, which damage the cells. The dose consequence to the sensitive organ like lungs of human body is considered in the present study to show the dose effect for various radionuclides from a hypothetical nuclear reactor accident. The calculations were made with the in-house developed computer program RaDARRA. Cardinal directions like E, ENE, ESE, N, NE, NNE, NNW, NW, S, SE, SSE, SSW, SW, W, WNW and WSW are considered to observe the dose effect along the directions. For the calculations, lungs dose arising from 8 radionuclides e.g., 89Sr, 91Y, 95Zr, 95Nb, 131I, 133I, 140Ba and 144Ce have been considered. Of all these radionuclides the maximum and minimum dose contribution mainly come from 144Ce (30%) and 95Nb (4.43%). It is marked that dose is maximum along North East (NE) direction for all the distances and for all types of the radioisotopes. Methodology used in the present study can also be utilized for any type of severe accident and any type of reactor power. DOI: http://dx.doi.org/10.3329/bjnm.v17i1.22489 Bangladesh J. Nuclear Med. 17(1): 30-37, January 2014